2012
DOI: 10.1021/jp208670v
|View full text |Cite
|
Sign up to set email alerts
|

Hindered Rotational Energy Barriers of BH4 Tetrahedra in β-Mg(BH4)2 from Quasielastic Neutron Scattering and DFT Calculations

Abstract: Metal borohydrides are of interest as hydrogen storage materials due to their high volumetric and gravimetric capacity. However, as with many of the complex hydrides, they are hampered by slow absorption and desorption kinetics and poor reversibility. 1À3 Among the borohydrides, Mg(BH 4 ) 2 ( Figure 1) and Ca(BH 4 ) 2 have more favorable thermodynamic stability than, for example, LiBH 4 , while maintaining attractive hydrogen storage capacities (14.9 and 11.5 mass %, respectively). 2,4 Furthermore, for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 60 publications
5
49
0
Order By: Relevance
“…This implies that, on the timescale of reorientational motions, BH 4 groups occupying positions belonging to the same Wyckoff site become inequivalent. Selective (site-specific) activation of disorder has previously been reported for the β-phase of Mg(BH 4 ) 2 [51]. Also for perovskite-related Y(BH 4 ) 3 solid state NMR studies have shown that BH 4 become dynamically inequivalent in spite of occuping the same Wyckoff site [32].…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…This implies that, on the timescale of reorientational motions, BH 4 groups occupying positions belonging to the same Wyckoff site become inequivalent. Selective (site-specific) activation of disorder has previously been reported for the β-phase of Mg(BH 4 ) 2 [51]. Also for perovskite-related Y(BH 4 ) 3 solid state NMR studies have shown that BH 4 become dynamically inequivalent in spite of occuping the same Wyckoff site [32].…”
mentioning
confidence: 80%
“…This is a comparable situation to that found in the polymorphs of Mg(BH 4 ) 2 , albeit in a very different underlying lattice. A recent combined QENS-DFT study deals with the thermally activated reorientations of BH 4 in Mg(BH 4 ) 2 [51]. The authors determine activation energies of 39 and 76 meV for jumps around the 2-fold (C 2 ) and 3-fold (C 3 ) axes, respectively.…”
mentioning
confidence: 99%
“…Ammonia stored in a safe manner is an attractive candidate as an energy carrier in vehicles [2e5] and as an ammonia reservoir for the selective catalytic reduction (SCR) of NO x gases in the vehicular exhaust [6]. Addition of metal borohydrides like LiBH 4 [7,8] or Mg(BH 4 ) 2 [9,10] to form the amine metal borohydrides (AMBs), enables a promising pathway for direct release of hydrogen upon heating, which is currently under intense investigation [11,12]. One of the most studied members of the amine family is Mg(NH 3 ) 6 Cl 2 [1,13], due to a high volumetric and gravimetric hydrogen capacity as well as good ab-and desorption kinetics [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties to overcome are reproducibility and aging, heat dissipation, time scales for charging and unloading, approaching ambient conditions for pressure and temperature during operation. In-situ and in-operando neutron diffraction is widely used, accompanied by quasielastic neutron scattering revealing diffusion mechanisms and rotational excitations [26][27][28][29][30].…”
Section: How To Get the Hydrogen Into The Tankmentioning
confidence: 99%